Prevalence and factors affecting symptoms of postpartum depression 6 months before and 6 months after the COVID-19 pandemic: A comparative study - Sedighe Karbalaei; Minoor Lamyian; Mohammad Eslami; Leyla Sahebi; Sahar Ansari (Payesh, 2024)
Objective(s): Postpartum depression is common in women. The present study was conducted with the aim of investigating and comparing the prevalence and factors affecting symptoms of postpartum depression in 6 months before and after the beginning of the covid-19 pandemic. Methods: This cross-sectional study compared symptoms of postpartum depression in 39724 women who gave birth 6 months before the COVID-19 pandemic and 6100 women who gave birth after the COVID-19 pandemic. The information related to the symptoms of postpartum depression was extracted from mental health screening records that are commonly used in health centers covered by the Ministry of Health. General information was obtained from the National Integrated Health System of the Ministry of Health and the data were analyzed in SPSS 22 software. Results: The prevalence of postpartum depressive symptoms 6 months before and 6 months after the COVID-19 pandemic was 1.9% and 2.6%, respectively. Symptoms of Postpartum depression 6 months before the COVID-19 pandemic significantly was associated with age, body mass index, history of infant death, unwanted pregnancy, the number of births (P<0.05), while symptoms of postpartum depression 6 months after the COVID-19 significantly was associated with education, unwanted pregnancy, the number of births (P<0.05). Based on multiple logistic regression analysis, the COVID-19 pandemic increased symptoms of postpartum depression [(OR=1.49, 95% CI: (1.12– 1.83)]. Conclusion: The COVID-19 pandemic influenced postpartum depression. The findings from the current study might be helpful in postpartum depressive symptoms management in the future crises.